2012 Solid-State, Actuators, and Microsystems Workshop Technical Digest 2012
DOI: 10.31438/trf.hh2012.130
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulated Thermionic Energy Converter With Stiffened Suspension

Abstract: This paper reports a prototype of a mechanically and thermally robust encapsulated microfabricated thermionic energy converter (μ-TEC). We used conformal sidewall deposition of poly-SiC to form stiff suspension legs with U-shaped cross sections, which increase the out-of-plane rigidity and prevent contact with the substrate during the heating of the suspended emitter-a qualitative improvement over the previously reported planar SiC μ-TECs [1]. Furthermore, we tested the new μ-TECs with both barium and barium o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…Our previous investigations demonstrated that Ba or BaO coating reduced the work function of the poly-SiC emitter to ∼2.1eV and increases the thermionic current by 5-6 orders of magnitude [25]. Our measurements for both the uncoated and the barium-coated poly-SiC emitter fit the Richardson-Dushman equation, when the uncoated poly-SiC emitter temperatures ranged from 2000-3000K and the barium-coated poly-SiC emitter temperatures ranged from 900-1400K:…”
Section: B Thermionic Emission Current Measurementssupporting
confidence: 67%
“…Our previous investigations demonstrated that Ba or BaO coating reduced the work function of the poly-SiC emitter to ∼2.1eV and increases the thermionic current by 5-6 orders of magnitude [25]. Our measurements for both the uncoated and the barium-coated poly-SiC emitter fit the Richardson-Dushman equation, when the uncoated poly-SiC emitter temperatures ranged from 2000-3000K and the barium-coated poly-SiC emitter temperatures ranged from 900-1400K:…”
Section: B Thermionic Emission Current Measurementssupporting
confidence: 67%